2016
DOI: 10.2298/tsci140715130d
|View full text |Cite
|
Sign up to set email alerts
|

Comparative performance analysis of experimental frigorific air conditioning system using R-134a and HFO-1234yf as a refrigerant

Abstract: In this study, to evaluate the comparative experimental performances, a frigorific air conditioning system using HFO1234yf and R134a was developed and refrigerated air was introduced into a conditioned room. The experiment was carried out at different condenser inlet temperatures and using the refrigerants at different charges, 1250, 1500, and 1750 grams. Experiments were conducted for a standard frigorific air conditioning system using the HFO1234yf and R-134a system. Air flow was introduced to the conditione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…When R1234yf was used in this study, the COP increased slightly compared with R134a. Direk et al [9][10][11][12][13] conducted an experiment to analyze the performance of R1234yf when used as an alternative refrigerant to R134a. In this study, a test bench consisting of two air-cooled heat exchangers, two expansion valves, a four-way valve, and a compressor was constructed using the equipment for an automobile air-conditioning system for a European compact automobile.…”
Section: Introductionmentioning
confidence: 99%
“…When R1234yf was used in this study, the COP increased slightly compared with R134a. Direk et al [9][10][11][12][13] conducted an experiment to analyze the performance of R1234yf when used as an alternative refrigerant to R134a. In this study, a test bench consisting of two air-cooled heat exchangers, two expansion valves, a four-way valve, and a compressor was constructed using the equipment for an automobile air-conditioning system for a European compact automobile.…”
Section: Introductionmentioning
confidence: 99%
“…The R1234yf can be used directly or with small modifications instead of R134a in AAC systems [3]. However, recent studies showed that the cooling capacity and COP values were about 4% ~ 18% and 1% ~ 15% lower when R1234yf used is in the system designed for R134a without any modification [4][5][6][7]. This is due to the R1234yf has between 21% and 28% lower latent heat of vaporization at the same saturation temperature in comparison with R134a.…”
Section: Introductionmentioning
confidence: 99%
“…Direk et al [18] carried out an experimental analysis to compare the performance of R134a and R1234yf using a frigorific air conditioning system at different amount of charges. They claimed that the time dependent temperature gradient is compatible for both refrigerants.…”
Section: Introductionmentioning
confidence: 99%